2018
DOI: 10.2136/sssaj2017.05.0139
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground and Root Decomposition of Cereal Rye and Hairy Vetch Cover Crops

Abstract: Hairy vetch decomposed faster than cereal rye. Hairy vetch released N within two weeks of termination. Biomass belowground decomposed more quickly than aboveground. Cover crop N release occurred earlier than maximum crop uptake due to late planting. Synchronizing cover crop decomposition and nutrient release with cash crop uptake can provide benefits to agroecosystems but can be difficult to implement. The objectives of this study were to quantify the aboveground and belowground decomposition and nutrient rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
141
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(149 citation statements)
references
References 34 publications
(54 reference statements)
6
141
1
1
Order By: Relevance
“…An ignored yet important management factor that can influence cover crop tissue C and N estimation is sample‐grinding size. A broad range of sample‐grinding size, ranging anywhere from >2 mm to pulverized have been reported in the literature (Jahanzad et al, 2016; Etemadi et al, 2017; Shelton et al, 2018; Sievers and Cook, 2018), but no agreement about which sampling size is the most appropriate has been reached to present. In a literature review, we randomly assessed 36 peer‐reviewed journal articles, which reported cover crop C and N concentrations (Table 1; in addition, see online version of article for supplemental material).…”
Section: Frequency Of Sample‐grinding Size In 36 Randomly Published Pmentioning
confidence: 99%
“…An ignored yet important management factor that can influence cover crop tissue C and N estimation is sample‐grinding size. A broad range of sample‐grinding size, ranging anywhere from >2 mm to pulverized have been reported in the literature (Jahanzad et al, 2016; Etemadi et al, 2017; Shelton et al, 2018; Sievers and Cook, 2018), but no agreement about which sampling size is the most appropriate has been reached to present. In a literature review, we randomly assessed 36 peer‐reviewed journal articles, which reported cover crop C and N concentrations (Table 1; in addition, see online version of article for supplemental material).…”
Section: Frequency Of Sample‐grinding Size In 36 Randomly Published Pmentioning
confidence: 99%
“…In order to prevent the loss of accumulated N, it is recommended to sow subsequent crops as soon as possible after incorporating the biomass of leguminous cover crops with low C:N ratios, such as hairy vetch. Sievers et al [26] pointed out that most of the N in hairy vetch tissues is released in the first two weeks after termination. Therefore, it is susceptible to leaching out or denitrification if the following crop is not planted on time or it is not able to reach the growth stage where it could use the N from hairy vetch.…”
Section: Spring Barley Yieldmentioning
confidence: 99%
“…Nitrate-N leaching losses were 0.35 g N m 2 for corn followed by cereal rye compared to 2.51 g N m 2 for corn followed by hairy vetch [77]. Legume cover crops like hairy vetch have lower C:N ratio (16:1 or 22:1 as in our study) that might decompose at a faster rate [78]. This could result in release of available N from the cover crop biomass that is not synchronized with maximum N demand of the cash crop and result in runoff/leaching and might increase N loading to the headwater streams.…”
Section: Overall Event Means Concentrationsmentioning
confidence: 42%